Application of Global Positioning System and microsensor technology in competitive Rugby League match-play: A systematic review and meta-analysis - Hausler, J.; Halaki, M.; Orr, R. (Sports Medicine, 2016)
The use of global positioning system (GPS) devices with the inclusion of microsenor technology in rugby league enables measurement of player activity profiles to understand the demands of match-play and optimise on-field performance.